The Study of Tawhid and its Influence on the Dimension of Religiosity - T. Wildan (Universitas Darussalam Gontor, 2022)
This study examines the influence of study tawhid on the dimension of religious of santri in Langsa City. The subject of the research was 125 santri of Salafiyah and integrated Islamic boarding schools. The research questions include; was there a correlation between study of tawhid carried out at the Islamic boarding schools and the dimension of religious of the santri in Langsa City. The researcher applied a mixed-method, which combined quantitative and qualitative approaches. Pearson product-moment was used to measure the validity of quantitative data and analytical descriptive was involved to analyze the qualitative data. Results showed that the correlation values between the students’ study of tawhid value and their dimension of religious at the Salafiah Islamic boarding school were; ideological 0,980, ritualistic 0,971, experiential 0,975, intellectuality 0,979, and consequential 0,926. All of the values were higher than r table, which was 0,278. This indicated that there was a significant correlation between the dimension of religious and the study of tawhid. While, results of students values at the integrated Islamic boarding school were ideological 0,941, ritualistic 0,951, experiential 0,944, intellectual 0,943, and consequential 0,910. The values were higher than r table, which was 0,403. This indicated that there was a significant correlation. The value of religiosity Sig (2-tailed) of Salafiyah and integrated boarding schools was 0,000 (p<0,01) thus the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This showed that there were significant correlations between the two variables.